A study on spending habits among DPA students of UiTM Sarawak / Deardrey Joyce Chimbi, Leha Saliman & Nor Shila Halu - Chimbi, Deardrey Joyce; Saliman, Leha; Halu, Nor Shila (2005)
The objective of our study is to identify spending habits among the students on how they spend their money. Apart from that, we determine the main source of financial resources of students. Besides that, our study encourages students to prepare personal budget planning as one alternative to mange their money in appropriate manner. In addition our study also required suggestion and recommendation on how to manage money. The main aim of our research is to analyze and determine spending habits attitude among target group and help them with our recommendation to upgrade their sensitivity upon the importance of budget planning and encounter overspend habits. The survey has been conducted through questionnaire distributed to 200 respondents but somehow we manage to gather only 152 questionnaires as our reference in conducting our research. We focused on part 4 until part 6 of DPA students because we believed that students at this level already reach maturity level and we trust them to give accurate and adequate information to support our research.